Terahertz radiation : Spectrally selective modulation of terahertz radiation beams. (30th November 2020) - Ushakov, A A; Matoba, M; Nemoto N; Kanda N; Konishi K; Panov, N A; Shipilo, D E; Chizhov, P A; Bukin, V V; Kuwata-Gonokami, M; Yumoto, J; Kosareva, O G; et al.
Abstract: We report the results of an experimental study on the focusing of broadband terahertz (THz) radiation using lenses and Fresnel zone plates. The obtained data are compared with the results of numerical simulations. It is shown that the use of lenses for focusing THz radiation can lead to the appearance of a ring structure in the spatial distributions of its intensity. The use of Fresnel zone plates allows the spatial distribution of the THz radiation intensity to be varied at selected frequencies of the spectrum.